Determining the relationship between "microvessel density" and different grades of astrocytoma based on immunohistochemistry for "factor VIII-related antigen" (von Willebrand factor) expression in tumor microvessels - Mahzouni Parvin; Mohammadizadeh Fereshteh; Mougouei Kourosh; Moghaddam Noushin; Chehrei Ali; Mesbah Alireza (Wolters Kluwer Medknow Publications, 2010)
Background: Astrocytic brain tumors are the most common primary central nervous system tumors, which are classified into four grades. One of the most important pathologic criteria for the diagnosis of higher-grade astrocytomas (especially glioblastoma multiforme) is microvessel proliferation, particularly in the form of glomeruloid complex. Because tumor angiogenesis is a necessary factor for growth and invasiveness of malignancies, microvessel density (MVD) and intensity of angiogenesis may be used to determine the grade of astrocytomas and plan therapy accordingly. We have planned this study to evaluate the relationship between vwf expression in microvessels and different grades of astrocytoma. Materials and Methods: Sixty-four formalin-fixed and paraffin-embedded blocks of surgical specimens with diagnosis of astrocytoma (grades I to IV, each of them 16 blocks) were selected in a simple-nonrandom sampling. Thin sections of tissue blocks underwent immunohistochemical staining for vwf. The stained slides were examined using a light microscope at low (100) and high (400) magnifications. MVD was estimated by calculating the mean number of stained microvessels in three areas of highest vascularization in the high-power field (400). The intensity of staining was determined based on a 3 scale model, in which scores 0, 1, 2, and 3 mean no detectable stain, trace staining, moderate amount of diffuse stain, and strong diffuse staining, respectively. Results: Thirty-six (56%) patients were male and 28 (44%) were female. Scores 0 and 1 of microvessel staining intensity were not observed in any grades studied, but severe staining intensity (score 3) was observed in 18.8%, 37.5%, 56.3%, and 87.5% of grades I, II, III, and IV astrocytomas, respectively. "Vwf vessel index" (MVD staining intensity of microvessels) was 23.84, 25.62, 31.62, and 62.43 in grades I, II, III, and IV astrocytomas, respectively. Conclusion: We found a significant relationship between staining intensity of vwf in microvessels and different grades of astrocytomas. The intensity of microvessel stain increases in parallel with increasing tumor grade. Regarding "microvessel density" and "vwf vessel index," the difference is predominantly between grade IV and all other grades. However, there is no other statistically meaningful difference between grades I, II and III.